2012
DOI: 10.1021/om200541z
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the [Cp2Mo(OH)(OH2)]+-Catalyzed Nitrile Hydration to Amides: A Theoretical Study

Abstract: Nitrile hydration to amides catalyzed by [Cp2Mo(OH)(OH2)]+ has been theoretically investigated by using acrylonitrile as a model and performing density functional theory calculations (B3LYP), both in the gas phase and in water solution. In both media, our results confirm the experimental belief that, among four plausible proposals, the intramolecular nucleophilic mechanism is the most favored for this kind of process. A hydrogen migration from oxygen to nitrogen atoms is the rate-limiting step in the gas phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Recent in‐depth theoretical studies on the hydrolysis of ethyl acetate, the acrylonitrile hydration, and the carbon monoxide oxidation catalyzed by [Cp 2 Mo(OH)(OH 2 )] + have been valuable to corroborate and rationalize the experimental belief that the intramolecular nucleophilic attack of the hydroxo ligand on the Mo‐coordinated substrate is the operative mechanism (see Scheme ) , , . In accordance with experimental suggestions,, this mechanism begins with the replacement of the aqua ligand of the catalytically active complex [Cp 2 Mo(OH)(OH 2 )] + by the substrate (XY in Scheme ).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Recent in‐depth theoretical studies on the hydrolysis of ethyl acetate, the acrylonitrile hydration, and the carbon monoxide oxidation catalyzed by [Cp 2 Mo(OH)(OH 2 )] + have been valuable to corroborate and rationalize the experimental belief that the intramolecular nucleophilic attack of the hydroxo ligand on the Mo‐coordinated substrate is the operative mechanism (see Scheme ) , , . In accordance with experimental suggestions,, this mechanism begins with the replacement of the aqua ligand of the catalytically active complex [Cp 2 Mo(OH)(OH 2 )] + by the substrate (XY in Scheme ).…”
Section: Introductionmentioning
confidence: 68%
“…More interestingly, those theoretical results have also shown that the rate‐determining step of this kind of organometallic processes depends on the organic substrate considered. Specifically, the attack of the hydroxo ligand is the most energy‐demanding step for the substrates acrylonitrile and carbon monoxide , . Kinetic trends found experimentally for the hydration of several nitriles could be satisfactorily rationalized from that theoretical fact .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…As only the product complex in this scheme could be experimentally detected, we also explored the alternative mechanism of general base catalysis, in which an external water molecule, which directly interacts with the hydroxide ligand, acts as a nucleophile for the attack on the Mo‐coordinated CO carbon atom. However, by taking into account experimental findings12,17,18 and our recent theoretical study on [Cp 2 Mo(OH)(OH 2 )] + ‐catalyzed nitrile hydration,40 we discarded other less likely mechanistic possibilities such as the attack of an external water molecule, which does not directly interact with the OH ligand, on the bound CO carbon atom.…”
Section: Resultsmentioning
confidence: 99%
“…26 kcal mol –1 )50 and more recently in the nitrile hydration catalyzed by [Cp 2 Mo(OH)(OH 2 )] + (ca. 15 kcal mol –1 ) 40. Finally, we also checked the effect of one explicit water molecule on TS3–R2_b along R2.…”
Section: Resultsmentioning
confidence: 99%